Age and employment in the new Member States - Mandl, Irene; Dorr, Andrea; Oberholzner, Thomas (Luxembourg, 2006)
"Over the last decade, Foundation research has examined effective ways of promoting the participation of older workers in the labour market, to enhance their contribution and productivity, and prevent their early exit and unemployment. This report extends the research to the new Member States and the acceding countries. It documents a range of almost 30 case examples from the new Member States, and from Bulgaria and Romania, which have implemented successful age management initiatives. The organisations concerned provide evidence of good practice in such areas as recruitment, training, skills development, time management, health promotion and workplace design. As well as documenting company initiatives, the report explores the role of public actors and initiatives in fostering active ageing."